2016
DOI: 10.1161/atvbaha.115.307034
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factor XI Promotes Distal Platelet Activation and Single Platelet Consumption in the Bloodstream Under Shear Flow

Abstract: Objective Coagulation factor XI (FXI) has been shown to contribute to thrombus formation on collagen or tissue factor (TF)-coated surfaces in vitro and in vivo by enhancing thrombin generation. Whether the role of the intrinsic pathway of coagulation is restricted to the local site of thrombus formation is unknown. This study was aimed to determine whether FXI could promote both proximal and distal platelet activation and aggregate formation in the bloodstream. Approach and Results Pharmacological blockade o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 32 publications
0
39
0
1
Order By: Relevance
“…Our previous work indicated that participation of the TF-triggered extrinsic pathway was required to generate enough thrombin to initiate the FXIa-dependent thrombin amplification mechanism, which can be interrupted by O1A6 (5). This FXI functionblocking antibody also reduced platelet aggregation downstream of thrombi formed on collagen/TF, suggesting a role of the FXI-thrombin axis in distal thrombi formation (57). Therefore, thrombin flux after 500 s is most likely augmented by the FXIa-dependent thrombin amplification loop.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous work indicated that participation of the TF-triggered extrinsic pathway was required to generate enough thrombin to initiate the FXIa-dependent thrombin amplification mechanism, which can be interrupted by O1A6 (5). This FXI functionblocking antibody also reduced platelet aggregation downstream of thrombi formed on collagen/TF, suggesting a role of the FXI-thrombin axis in distal thrombi formation (57). Therefore, thrombin flux after 500 s is most likely augmented by the FXIa-dependent thrombin amplification loop.…”
Section: Discussionmentioning
confidence: 96%
“…Pharmacologic FXI inhibition does not reduce local platelet adhesion in tissue factor and collagen-coated capillary tubes, but reduces platelet activation and aggregation downstream of the growing thrombus. 52 Similarly, in an arteriovenous shunt model of thrombosis in non-human primates, neither anti-FXI antibodies nor ASOs alter platelet deposition on a collagen-rich segment of graft, but both decrease thrombus propagation (platelet accumulation and fibrin deposition) downstream of the collagen-rich region. 53,54 A promising phase I clinical trial demonstrated success of anti-FXI ASO treatment in humans undergoing elective total knee arthroplasty; ASO-mediated reduction of plasma FXI levels decreased symptomatic or asymptomatic venous thrombosis/thromboembolism (VTE) incidence, and the higher ASO dose tested was superior to enoxaparin.…”
Section: Effects Of Antithrombotic and Hemostatic Agents On Fibrinmentioning
confidence: 98%
“…Moreover, our work suggests that activation of the coagulation factors XI and X play a key role in promoting thrombin generation, platelet activation and microaggregate formation in the bloodstream. 23 …”
Section: Discussionmentioning
confidence: 99%